Joint forest management in India: a game theoretic analysis of its evolution and reasons behind poor performance - Saha, D.; Taron, Avinandan (2021)
India initiated Joint Forest Management in 1990, by the National Forest Policy of 1988. It stressed on the involvement of partnership between the Forest Department and local communities for sustainable forest management. This study utilises a game theoretic framework to describe the evolution of this system, and its present structural problems. The model indicates conditions of improvement within the institution to make it sustainable. These recommendations are based on certain assumptions of the existing situation. Therefore, using the conclusion for policy recommendations needs a thorough appreciation of complexities existing in the system, which has been simplified in the model.